Adhesive composition and connection structure
By adjusting the compression hardness of conductive particles and the area ratio of surface protrusions, the problem of increasing the connection resistance of electronic components under high temperature and high humidity conditions is solved, and a high-reliability connection structure is achieved.
Patent Information
- Application Number
- JP2023162681
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-07
AI Technical Summary
Under high temperature and high humidity conditions, the connection resistance of the electronic component is easily increased, especially when the electrode of one of the electronic components consists of a harder conductive layer (such as the Ni layer) and a softer conductive layer (such as the Au layer), and the soft conductive layer is thinner, the reliability of the connection is difficult to ensure.
By adjusting the compression hardness of the conductive particles and the area ratio of the surface protrusion, the conductive particles are deformed under heating and pressure, increasing the contact area with the electrode, thereby improving the reliability of the connection. Specific measures include forming a multi-layer conductive layer on the surface of the conductive particles, and ensuring that the conductive particles can effectively contact the electrode during the connection process by adjusting the thickness of the metal layer and the area ratio of the protrusions.
It realizes the low connection resistance under high temperature and high humidity conditions, improves the reliability of electronic components connection, and ensures stability and good conductivity between electronic components.
Smart Images

Figure 2025053637000002 
Figure 2025053637000003 
Figure 2025053637000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition and a connection structure. [Background technology]
[0002] In the field of micro OLEDs used for AR / VR applications, anisotropic conductive films are used to connect electronic components and fine circuit electrodes. Anisotropic conductive films are made, for example, by dispersing conductive particles in an adhesive film. By sandwiching such anisotropic conductive films between opposing electrodes and applying heat and pressure, it is possible to electrically connect the opposing electrodes while maintaining the insulation between adjacent electrodes on the same substrate.
[0003] There are various known structures of electrodes connected by anisotropic conductive films. For example, Patent Document 1 describes a semiconductor device having a protruding electrode with a two-layer structure in which a first conductive layer and a second conductive layer formed on the first conductive layer are laminated, and the second conductive layer is made of a material that is lower in hardness than the first conductive layer.
[0004] On the other hand, in anisotropic conductive films, conductive particles having protrusions on their surfaces are sometimes used as the conductive particles. For example, Patent Document 1 discloses an adhesive composition that contains an adhesive component and conductive particles, the conductive particles having plastic particles and a metal layer covering the plastic particles, the conductive particles having a plurality of protrusions formed on their surfaces, and the height of the plurality of protrusions being 85 to 1200 nm on average. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2000-286299 A [Patent Document 2] International Publication No. 2018 / 199329 Summary of the Invention [Problem to be solved by the invention]
[0006] According to the study by the present inventors, when at least one electrode of two electronic components to be connected is composed of a relatively hard conductive layer (e.g., a Ni layer) and a relatively soft conductive layer (e.g., an Au layer) formed on the surface of the hard conductive layer (the outermost surface of the electrode), and the thickness of the soft conductive layer is thin, it has become clear that the connection resistance between the connected electronic components is more likely to increase when placed under high temperature and high humidity conditions (e.g., a temperature of 85°C and a humidity of 85%) for a long period of time, compared to when the thickness of the soft conductive layer is thick. The adhesive composition is required to suppress the increase in resistance even in the connection of such electronic components (to have excellent connection reliability).
[0007] Therefore, one aspect of the present invention aims to provide an adhesive composition that has a soft conductive layer on its outermost surface and that has excellent connection reliability when used to connect electrodes in which the conductive layer is thin. [Means for solving the problem]
[0008] As a result of further investigations aimed at solving the above-mentioned problems, it was found that when the soft conductive layer on the outermost surface of the electrode is thick, the soft conductive layer deforms to conform to the shape of the conductive particles when heated and pressed during mounting, resulting in a wide area of contact between the electrode and the conductive particles and stable, good conductivity; whereas, when the soft conductive layer on the outermost surface of the electrode is thin, the conductive layer is less likely to deform, resulting in a small area of contact between the electrode and the conductive particles, which is one of the reasons why the connection resistance is likely to increase under high temperature and high humidity conditions.
[0009] Therefore, we tried to reduce the compression hardness of the conductive particles to flatten them when pressure is applied and increase the contact area between the electrode and the conductive particles. However, it became clear that if the compression hardness of the conductive particles is too low, the protrusions of the conductive particles do not sufficiently penetrate into the electrode, and good conductivity may not be obtained.
[0010] The inventors conducted further intensive research and discovered that by setting the compression hardness of the conductive particles and the ratio of the area of the protrusions of the conductive particles within a specific range, it is possible to ensure a sufficient contact area between the electrode and the conductive particles while allowing the protrusions of the conductive particles to fully penetrate into the electrode surface, thereby improving connection reliability under high temperature and high humidity conditions, and thus completing the present invention.
[0011] In some aspects, the present invention provides the following [1] to [7]. [1] The conductive particles have multiple protrusions on their surfaces, and the compression hardness of the conductive particles when compressed by 20% is 350 kgf / mm 2 ~1500kgf / mm 2 and the ratio of the area of the plurality of protrusions to the area of the surface of the conductive particle is 30% or more. [2] A connection structure comprising: a first electronic component having a first electrode; a second electronic component having a second electrode; and a connection portion disposed between the first electronic component and the second electronic component and electrically connecting the first electrode and the second electrode to each other, wherein the connection portion comprises a cured product of the adhesive composition described in [1]. [3] The connection structure according to [2], wherein at least one of the first electrode and the second electrode has a surface layer containing Au. [4] The connection structure according to [3], wherein the thickness of the surface layer is 3 μm or less. [5] A method for producing a connection structure, comprising: a step of placing the adhesive composition described in [1] between a first electronic component having a first electrode and a second electronic component having a second electrode; and a step of thermocompression bonding the first electronic component and the second electronic component via the adhesive composition to electrically connect the first electrode and the second electrode to each other. [6] A method for manufacturing a connection structure according to [5], wherein at least one of the first electrode and the second electrode has a surface layer containing Au. [7] The method for producing a connection structure according to [6], wherein the thickness of the surface layer is 3 μm or less. Effect of the Invention
[0012] According to one aspect of the present invention, it is possible to provide an adhesive composition which has a soft conductive layer on its outermost surface and which exhibits excellent connection reliability when used to connect electrodes in which the conductive layer is thin. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic cross-sectional view showing one embodiment of an adhesive film. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of a conductive particle. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing another embodiment of an adhesive film. [Figure 4] FIG. 1 is a schematic cross-sectional view showing one embodiment of a connection structure. [Diagram 5] 5A to 5C are schematic cross-sectional views showing one embodiment of a method for producing a connection structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0015] <Adhesive composition> The adhesive composition according to one embodiment contains conductive particles having a plurality of protrusions on the surface thereof, and the conductive particles have a compression hardness of 350 to 1500 kgf / mm 2 and the ratio of the area of the protrusions to the area of the surface of the conductive particles is 30% or more.
[0016] The adhesive composition usually further contains an adhesive component, and conductive particles are dispersed in the adhesive component. The adhesive composition may be in the form of a paste or a film. FIG. 1 is a schematic cross-sectional view showing one embodiment of a film-like adhesive composition (adhesive film). As shown in FIG. 1, in one embodiment, the adhesive film 1 is composed of a single layer consisting of an adhesive component (insulating adhesive) 2 and conductive particles 3 dispersed in the adhesive component 2.
[0017] Fig. 2 is a cross-sectional view showing a schematic diagram of an embodiment of a conductive particle 3. As shown in Fig. 2(a), in one embodiment, a conductive particle 30A has a non-conductive core 31 and a conductive layer 32A that covers the core 31.
[0018] It is preferable that substantially the entire surface of core body 31 is covered with conductive layer 32A, but a portion of the surface of core body 31 may be exposed and not covered with conductive layer 32A, as long as the function of electrically connecting electronic components to each other is maintained.
[0019] The core 31 is formed of a non-conductive material such as glass, ceramic, or resin, and is preferably formed of resin. Examples of resin include acrylic resin, styrene resin, silicone resin, polybutadiene resin, and copolymers of monomers constituting these resins. The core 31 may be a particle containing a polymer containing at least one monomer selected from styrene and divinylbenzene as a monomer unit. The polymer may further contain (meth)acrylate as a monomer unit. The diameter of the core 31 may be, for example, 1 μm or more, or 2 μm or more on average, and may be 40 μm or less, 30 μm or less, or 20 μm or less.
[0020] The conductive layer 32A is, for example, made of one conductive layer. The conductive layer 32A is, for example, made of Ni, Cu, Ag, Ru, or Pd, or an alloy containing these metal elements. The alloy may be, for example, an alloy containing Ni (Ni alloy). Examples of Ni alloys include Ni-B, Ni-P, and Ni-WB. From the viewpoint of further suppressing the decrease in connection reliability when the soft conductive layer on the outermost surface is used for connecting an electrode having a thin thickness, the conductive layer 32A is preferably made of Pd. The thickness of the conductive layer 32A may be, for example, 50 nm or more and 300 nm or less. The thickness of the conductive layer 32A means the thickness of the conductive layer at a portion where a protrusion portion described later is not formed. The thickness of the conductive layer 32A can be measured by an electron microscope.
[0021] 2(b), in a conductive particle 30B according to another embodiment, the conductive layer 32B may be a two-layer conductive layer consisting of a first conductive layer 32a and a second conductive layer 32b. That is, the conductive particle 30B according to another embodiment includes a core 31, a first conductive layer 32a that covers the core 31, and a second conductive layer 32b that covers the first conductive layer 32a.
[0022] The first conductive layer 32a is made of, for example, Ni. The second conductive layer 32b may be made of, for example, Au or Pd. That is, the conductive particle 30B may have a layer made of Au or Pd on the outermost surface side of the conductive particle 30B as a conductive layer.
[0023] The thickness of the first conductive layer 32a may be, for example, 50 nm or more and 300 nm or less. The thickness of the second conductive layer 32b may be, for example, 2 nm or more, 5 nm or more, or 10 nm or more, and 200 nm or less, 100 nm or less, or 50 nm or less. The thicknesses of the first conductive layer 32a and the second conductive layer 32b each refer to the thickness of a portion of the conductive layer where a protrusion, which will be described later, is not formed. The thicknesses of the first conductive layer 32a and the second conductive layer 32b can be measured by an electron microscope.
[0024] A plurality of protrusions 33 are formed on the surface of the conductive particle 3. In the conductive particle 30A shown in Fig. 2(a), the protrusions 33A are composed of a single conductive layer 32A. In the conductive particle 30B shown in Fig. 2(b), the protrusions 33B are composed of a two-layer conductive layer 32B consisting of a first conductive layer 32a and a second conductive layer 32b.
[0025] The ratio of the area of the multiple protrusions 33 to the area of the surface of the conductive particle 3 (protrusion area ratio) is 30% or more. From the viewpoint of expanding the contact area between the conductive particle and the electrode and further improving the connection reliability, the protrusion area ratio may be 32% or more, 35% or more, 38% or more, or 40% or more. In addition, the protrusion area ratio may be 70% or less, 65% or less, 60% or less, or 55% or less.
[0026] The area ratio of the protrusions is determined by analyzing a black-and-white SEM image of the conductive particles 3 generated by imaging using a scanning electron microscope (SEM). The analysis of the SEM image can be performed using the method described in JP 2016-61722 A. Specifically, the area ratio of the protrusions can be determined by a method including the steps of: detecting a particle edge, which is a boundary between a projected image of each conductive particle 3 and other regions in an SEM image in which a plurality of conductive particles 3 are imaged; calculating a second threshold value corresponding to the boundary between the protrusions and other regions from a frequency distribution of brightness in the region inside the particle edge; binarizing the region inside the particle edge using the obtained second threshold value to generate a binary image; calculating the ratio of the area of the region corresponding to the protrusions to the area inside the particle edge in the obtained binary image as the area ratio of the protrusions of each conductive particle 3; and calculating an average value of the area ratios of the protrusions calculated for 100 conductive particles 3.
[0027] In the above analysis of the SEM image, the particle edge substantially corresponds to the outer periphery of the two-dimensional projection image of the conductive particle 3, including the unevenness resulting from the protrusion. The frequency distribution of the brightness obtained from the SEM image generally shows a minimum value reflecting the particle edge portion. The SEM image is binarized using the brightness corresponding to this minimum value as a first threshold value to generate a binarized image. The edge formed in the obtained binarized image is detected as the particle edge. The central coordinates of the conductive particle 3 on the SEM image are calculated based on the particle edge. A circle fitting to the particle edge is obtained by the least squares method, and the center of the circle is set as the central coordinates of the conductive particle 3, and the radius of the circle is obtained as r. Then, a circular region of radius r / 2 centered on the central coordinates is identified as the region inside the particle edge.
[0028] In the frequency distribution of luminance in the region inside the particle edge, generally, the luminance value of the pixel included in the region including the particle surface and the part excluding the edge of the protrusion is mainly reflected on the low luminance side, and the luminance value of the pixel included in the region of the edge part of the protrusion is mainly reflected on the high luminance value side. And, on the low luminance value side, there is a mountain of frequency representing the part excluding the particle surface and the edge of the protrusion, and on the high luminance value side, there is a part with the maximum rate of decrease of the frequency indicating that the part excluding the particle surface and the edge of the protrusion decreases rapidly as the luminance increases. Based on such a frequency distribution, the second threshold is selected between the luminance value corresponding to the maximum value of the frequency on the low luminance side and the luminance value corresponding to the part with the maximum rate of decrease of the frequency on the high luminance side. More specifically, the second threshold is set to a luminance value intermediate between the luminance value corresponding to the maximum value of the frequency on the low luminance side and the luminance value corresponding to the point with the maximum rate of decrease of the frequency on the high luminance side. Based on the second threshold value, a binary image of the area inside the particle edge is generated, and the ratio of the area of the white area in the binary image to the area inside the particle edge is calculated as the area ratio of the protrusion of each conductive particle 3.
[0029] The average height of the multiple protrusions 33 may be 50 nm or more, 70 nm or more, 90 nm or more, 110 nm or more, or 130 nm or more, and may be 1200 nm or less, 1000 nm or less, 600 nm or less, 500 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, or 150 nm or less.
[0030] The average height of the plurality of protrusions 33 can also be determined by analyzing the SEM image of the conductive particles according to the method described in JP 2016-61722 A. Specifically, for example, the average height can be determined by a method including a step of detecting a particle edge, which is a boundary between the projected image of each conductive particle 3 and other regions in an SEM image in which a plurality of conductive particles 3 are captured, a step of calculating the central coordinates of the conductive particles 3 on the SEM image based on the particle edge, a step of dividing the particle edge into 18 particle edge parts in which an area of 40 degrees in polar coordinates centered on the central coordinates is shifted by 20 degrees, a step of calculating the difference between the maximum and minimum values of the distance between the central coordinates and the particle edge for each particle edge part, and a step of calculating the average value of these differences as the average height of the protrusions 33, and a step of calculating the average height of the protrusions 33 for 100 conductive particles 3 and calculating the average value.
[0031] In the above analysis of SEM images, the maximum distance between the center coordinate and the particle edge for each particle edge part is found by selecting the three points that make up the edge of each particle edge part with the largest distance from the center coordinate and calculating the average value. Also, the minimum distance between the center coordinate and the particle edge for each particle edge part is found by selecting the three points that make up the edge of each particle edge part with the smallest distance from the center coordinate and calculating the average value.
[0032] The average particle size of the conductive particles 3 may be 1.0 μm or more, 2.0 μm or more, 2.5 μm or more, 3.0 μm or more, or 3.2 μm or more, and may be 10 μm or less, 8.0 μm or less, 6.0 μm or less, 5.0 μm or less, or 4.0 μm or less. In this specification, the particle size of any 300 pieces (pcs) of conductive particles 3 is measured by observation using a scanning electron microscope (SEM), and the average value of the obtained particle sizes is defined as the average particle size. More specifically, the average particle size of the conductive particles 3 is obtained by finding a circle that fits the particle edge of each conductive particle 3 in the SEM image of the conductive particles 3 as described above using the least squares method, and the diameter of the circle is defined as the particle size of each conductive particle 3, and the average value of the particle sizes of the 300 conductive particles 3 is calculated.
[0033] The compression hardness of the conductive particles 3 when compressed by 20% is 350 kgf / mm 2 ~1500kgf / mm 2 The compression hardness of the conductive particles 3 when compressed by 20% is 380 kgf / mm 2 Over 400kgf / mm 2 Over 420kgf / mm 2 or more than 450kgf / mm 2 or more, 1300 kgf / mm 2 Below, 1200kgf / mm 2 Below 1100kgf / mm 2 Below 1000kgf / mm 2 Below, 900kgf / mm 2 or less than 800kgf / mm 2 or less. The greater the compression hardness of the conductive particles 3, the easier it is for the protrusions of the conductive particles to be embedded into the electrode surface when the adhesive composition is used as an anisotropic conductive adhesive composition, which is preferable. On the other hand, the smaller the compression hardness of the conductive particles, the easier it is for the conductive particles to be flattened and the larger the contact area between the electrode and the conductive particles, which is preferable when the adhesive composition is used as an anisotropic conductive film.
[0034] The compression hardness (hereinafter sometimes referred to as "K value") of the conductive particles 3 is measured using a surface hardness compression measuring device (for example, HM2000, manufactured by Fisher Instruments Inc.). Specifically, the conductive particles 3 are first scattered on a slide glass (S1214, manufactured by Matsunami Glass Industrial Co., Ltd.) on a stage set at 25°C. Then, one conductive particle 3 is selected from the particles and compressed from the center at a speed of 0.33 mN / sec with an initial load of 0.1 mN using a diamond indenter in the shape of a rectangular column with a square base of 50 μm on a side. The K value can be calculated from the stress-strain curve. Specifically, the compression equation of an elastic sphere is given by: F=(2 1 / 2 / 3)×(S 3 / 2 )×(E×R 1 / 2 ) / (1-σ2 ) Using the following formula K = E / (1-σ 2 )=(3 / 2 1 / 2 )×F×(S -3 / 2 )×(R -1 / 2 ) Furthermore, if the deformation rate is X (%) and the diameter of the sphere is D (μm), the following formula can be used: K = 3000F / (D 2 X 3 / 2 ) x 10 6 The K value at any deformation rate can be calculated by the following formula. It is calculated by X=(S / D)×100. The compression hardness of the conductive particles 3 when compressed by 20% means the K value when the deformation rate X is 20(%). The maximum test load in the compression test is set to, for example, 50 mN.
[0035] The recovery rate of the conductive particles 3 may be 10% or more, 20% or more, 25% or more, or 30% or more, and may be 100% or less, 90% or less, 80% or less, 75% or less, or 70% or less.
[0036] The recovery rate of the conductive particles 3 is measured using a surface hardness compression measuring device (e.g., HM2000, manufactured by Fisher Instruments Inc.). Specifically, the conductive particles 3 are first scattered on a slide glass (S1214, manufactured by Matsunami Glass Industrial Co., Ltd.) on a stage set at 25°C. Then, one conductive particle 3 is selected from the selected particles, and compressed from the center at a speed of 0.33 mN / sec with an initial load of 0.1 mN using a diamond indenter having a square base with sides of 50 μm, until a load of 5 mN is applied, and then the load is reduced inversely to the initial load at a speed of 0.33 mN / sec. Here, the displacement of the conductive particle 3 from the initial load (load 0.1 mN) to the load reversal (load 5 mN) is defined as L2, and the displacement of the conductive particle 3 from the load reversal to the final load (load 0.1 mN) is defined as L1, and the value of L1 / L2×100(%) is calculated as the recovery rate of the conductive particle 3. This operation is performed for 10 conductive particles 3 and the average value is calculated to calculate the recovery rate of the conductive particles 3 in this embodiment.
[0037] The conductive particle 3 having the protrusions as described above can be obtained, for example, by forming conductive layers 32A, 32B by metal plating on the surface of the core 31. During the metal plating, the plating conditions can be changed to vary the thickness of the conductive layers 32A, 32B, thereby forming the protrusions 33. For example, the concentration of the plating solution can be gradually increased during the metal plating process, thereby forming the protrusions 33.
[0038] Alternatively, a conductive layer having bump-like protrusions can be formed by adjusting the pH of the plating solution, for example, by setting the pH of a nickel plating solution to 6 (see Mochizuki et al., Surface Technology, Vol. 48, No. 4, pp. 429-432, 1997). When glycine is used as a complexing agent that contributes to the stability of the plating bath, a conductive layer having a flat surface is formed, whereas when tartaric acid or DL-malic acid is used as a complexing agent, bump-like protrusions are formed (see, for example, Ogihara et al., Amorphous Plating, Vol. 36, pp. 35-37, 1994; Ogihara et al., Journal of the Institute of Circuit Packaging, Vol. 10, No. 3, pp. 148-152, 1995). By employing these methods, conductive layers 32A and 32B having protrusions 33 can be formed.
[0039] When producing the conductive particle 30B shown in FIG. 2(b), for example, a first conductive layer 32a having protrusions can be formed by the above-mentioned method, and then a layer of Au or Pd can be formed by displacement plating to obtain a second conductive layer 32b.
[0040] The area ratio of the protrusions in the conductive particles 3 can be adjusted, for example, by adjusting the concentration when the concentration of the plating solution is increased stepwise during the metal plating process. For example, the reaction can be accelerated by suddenly increasing the concentration of the plating solution, and the area ratio of the protrusions can be increased. Furthermore, the compression hardness of the conductive particles can be adjusted, for example, when the core is made of a resin, by appropriately adjusting the type of resin (when the resin is a copolymer, the copolymerization ratio of monomers).
[0041] Furthermore, the conductive particle 3 having the above-mentioned protrusions can also be obtained, for example, by disposing an insulating or conductive core material on the surface of the core 31 and then forming the conductive layers 32A, 32B by metal plating. In this case, the area ratio of the protrusions in the conductive particle 3 can also be adjusted, for example, by the amount of the core material disposed on the surface of the core 31.
[0042] The content of the conductive particles 3 may be 5 mass % or more, 10 mass % or more, and may be 30 mass % or less, or 25 mass % or less, based on the total mass of the solid content in the adhesive composition.
[0043] The content of the conductive particles 3 may be 1 vol % or more, 50 vol % or less, or 40 vol % or less, based on the total volume of the solid content in the adhesive composition.
[0044] The adhesive component 2 is, for example, made of a material that has insulating properties and exhibits heat or light curing properties. The adhesive component 2 may contain a polymerizable substance having a functional group that polymerizes by radicals. An example of the polymerizable substance is (meth)acrylate.
[0045] Examples of (meth)acrylates include urethane (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, dimethylol tricyclodecane diacrylate, trimethylol propane triacrylate, tetramethylol methane tetraacrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxypolyethoxy)phenyl]propane, dicyclopentenyl acrylate, tricyclodecanyl acrylate, bis(acryloxyethyl)isocyanurate, ε-caprolactone-modified tris(acryloxyethyl)isocyanurate, tris(acryloxyethyl)isocyanurate, and ethylene oxide-modified di(meth)acrylate phosphate. When ethylene oxide-modified di(meth)acrylate phosphate is used as the (meth)acrylate, the adhesive strength of the adhesive composition can be further improved.
[0046] The adhesive component 2 may contain only (meth)acrylate as a polymerizable substance, or may contain other polymerizable substances other than (meth)acrylate. The polymerizable substance is a substance having a functional group that is polymerized by a radical. An example of the other polymerizable substance is a maleimide compound.
[0047] The content of the polymerizable substance may be 10% by mass or more, 20% by mass or more, 30% by mass or more, or 40% by mass or more, and may be 80% by mass or less, 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the total mass of the adhesive component 2.
[0048] The adhesive component 2 may contain a curing agent (thermal radical polymerization initiator). The curing agent is a compound that decomposes when heated to generate free radicals.
[0049] Examples of the curing agent include peroxides and azo compounds. Examples of the peroxides include diacyl peroxides such as dioctanoyl peroxide, dilauroyl peroxide, distearoyl peroxide, and dibenzoyl peroxide; peroxydicarbonates such as bis(4-t-butylcyclohexyl) peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, and di-2-ethylhexyl peroxydicarbonate; t-butyl peroxypivalate, t-hexyl peroxypivalate, and the like. peroxy-2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisobutyrate, t-hexylperoxyisopropylmonocarbonate, t-butylperoxy-3,5,5-trimethylhexanoate, t peroxy esters such as t-butyl peroxylaurate, t-butylperoxy-2-ethylhexyl monocarbonate, t-butyl peroxybenzoate, t-hexyl peroxybenzoate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, and t-butyl peroxyacetate; peroxy ketals such as 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)-2-methylcyclohexane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, and 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane; dialkyl peroxides such as dicumyl peroxide, t-butylcumyl peroxide, and di-t-butyl peroxide; and hydroperoxides such as p-menthane hydroperoxide.
[0050] Examples of azo compounds include 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, and the like.
[0051] As the curing agent, one of the above peroxides and azo compounds may be used alone, or two or more of them may be used in combination. The adhesive component preferably contains at least one of diacyl peroxide and peroxy ester as the curing agent. The one-minute half-life temperature of the diacyl peroxide and the peroxy ester may be independently 90 to 175°C. The molecular weight of the diacyl peroxide and the peroxy ester may be independently 180 to 1000.
[0052] The content of the curing agent may be 0.05 mass% or more, 0.1 mass% or more, 1 mass% or more, or 2 mass% or more, and may be 20 mass% or less, 10 mass% or less, or 8 mass% or less, based on the total mass of the adhesive component 2.
[0053] The adhesive component 2 may contain a thermoplastic resin. Examples of the thermoplastic resin include polyamide resin, phenoxy resin, (meth)acrylic resin, polyimide resin, polyester resin, polyurethane resin, polyester urethane resin, and polyvinyl butyral resin. These thermoplastic resins may be used alone or in combination of two or more.
[0054] The content of the thermoplastic resin may be 20% by mass or more and 50% by mass or less based on the total mass of the adhesive component 2.
[0055] The adhesive component 2 may further contain other components such as a cure regulator, an adhesion promoter, a coupling agent (such as a silane coupling agent), an ion trapping agent, a visibility agent, a dispersant, a photoradical polymerization initiator, a filler, etc. The content of the other components may be, for example, 1% by mass or more and 20% by mass or less based on the total mass of the adhesive component.
[0056] In other embodiments, the adhesive film may have two or more regions. The adhesive film may include a first region including a first adhesive component and a second region adjacent to the first region including a second adhesive component. Each of the first region and the second region may be a layer.
[0057] For example, as shown in FIG. 3, the adhesive film 1 may have a two-layer structure including a layer containing conductive particles 3A (a first adhesive layer consisting of an adhesive component 2A and conductive particles 3A dispersed in the adhesive component 2A) 1A and a layer not containing conductive particles (a second adhesive layer consisting of an adhesive component 2B) 1B. In this case, the first adhesive layer 1A may contain the above-mentioned polymerizable substance, curing agent, curing regulator, thermoplastic resin, conductive particles, and other components as necessary. The second adhesive layer 1B may contain the above-mentioned polymerizable substance, curing agent, curing regulator, thermoplastic resin, and other components as necessary. The types of components contained in the second adhesive layer 1B may be the same as or different from those in the first adhesive layer 1A.
[0058] The contents of the polymerizable substance, curing agent, curing regulator, thermoplastic resin, and other components in the first adhesive layer and the second adhesive layer may each independently be the same as the contents of each component in the adhesive composition described above. In this case, "based on the total mass of the adhesive components" is to be read as "based on the total mass of the adhesive components contained in the first adhesive layer" or "based on the total mass of the adhesive components contained in the second adhesive layer."
[0059] The density of the conductive particles 3 in the adhesive film 1 is 1000 particles / mm 2 More than 3000 pieces / mm 2 More than 5000 pieces / mm 2 More than 7000 pieces / mm 2 or more than 8000 pieces / mm 2 or more, and 2 Below, 13000 pieces / mm 2 Below, 12000 pieces / mm 2 or less than 11000 pieces / mm2 The number density of the conductive particles 3 is determined by counting the number of conductive particles 3 per unit area of the adhesive film 1 using an electron microscope.
[0060] The thickness of the adhesive film 1 may be, for example, 5 μm or more, or 10 μm or more, and may be 50 μm or less, 30 μm or less, or 20 μm or less.
[0061] The adhesive composition (adhesive film 1) may be a conductive adhesive composition (conductive adhesive film) or an anisotropic conductive adhesive composition (anisotropic conductive adhesive film). The adhesive composition can be suitably used for producing a connection structure.
[0062] <Connection structure> A connection structure according to one embodiment includes a first electronic component having a first electrode, a second electronic component having a second electrode, and a connection portion disposed between the first electronic component and the second electronic component and electrically connecting the first electrode and the second electrode to each other, wherein the connection portion includes a cured product of the adhesive composition described above.
[0063] Fig. 4 is a schematic cross-sectional view showing one embodiment of a connection structure. As shown in Fig. 4, a connection structure 10 includes a first electronic member 4 and a second electronic member 5 facing each other, and a connection portion 6 connecting the first electronic member 4 and the second electronic member 5 between the first electronic member 4 and the second electronic member 5.
[0064] The first electronic component 4 includes a first substrate 41 and a first electrode 42 formed on a main surface 41a of the first substrate 41. The second electronic component 5 includes a second substrate 51 and a second electrode 52 formed on a main surface 51a of the second substrate 51.
[0065] There is no particular limitation on the first electronic member 4 and the second electronic member 5 as long as they are members having electrodes that require electrical connection. Examples of members having electrodes include active elements such as a diode such as a micro OLED, a semiconductor chip, a transistor, and a thyristor, passive elements such as a capacitor, a resistor, and a coil, and a substrate having electrodes such as a printed circuit board.
[0066] The first substrate 41 and the second substrate 51 may be a silicon substrate, a glass substrate, a flexible substrate, etc. The flexible substrate may contain at least one thermoplastic resin selected from the group consisting of, for example, polyimide (PI), polyethylene terephthalate (PET), polycarbonate (PC), and polyethylene naphthalate (PEN).
[0067] Examples of electrode materials for forming the first electrode 42 and the second electrode 52 include metals such as Ag, Ni, Al, Au, Cu, Ti, and Mo, metal oxides such as ITO and IZO, and conductors such as silver nanowires and carbon nanotubes. The first electrode 42 and the second electrode 52 may be made of the same material or different materials.
[0068] In one embodiment, the first electrode 42 may include a base layer provided on the first substrate 41 and a surface layer provided on the base layer. In another embodiment, the second electrode 52 may include a base layer provided on the second substrate 51 and a surface layer provided on the base layer. These surface layers are located on the outermost surfaces of the first electrode 42 and the second electrode 52, respectively. Either the first electrode 42 or the second electrode 52 may include a base layer and a surface layer, or both the first electrode 42 and the second electrode 52 may include a base layer and a surface layer.
[0069] The base layer may include a hard metal such as Ni, and the surface layer may include a soft metal such as Au, Pd, etc. The hardness of the surface layer may be less than that of the base layer.
[0070] The thickness of the surface layer may be 0.005 μm or more, or 0.01 μm or less, and may be 5 μm or less, or 3 μm or less. In an adhesive film according to an embodiment, the compression hardness of the conductive particles and the area ratio of the protrusions of the conductive particles are within a specific range, so that even if the electrode has a base layer made of a hard metal and the surface layer is thin, the contact area between the electrode and the adhesive film is sufficiently large and the protrusions of the conductive particles are easily embedded in the electrode.
[0071] The first electronic member 4 and the second electronic member 5 may each be provided with one first electrode 42 or one second electrode 52, but preferably a large number of electrodes are provided at predetermined intervals.
[0072] The connection portion 6 contains an insulating material 7, which is a cured product of an adhesive composition, and conductive particles 3. The conductive particles 3 may be disposed not only between the opposing first electrode 42 and second electrode 52, but also between the main surface 41a of the first substrate 41 and the main surface 51a of the second substrate 51. In the connection structure 10, the first electrode 42 and the second electrode 52 are electrically connected via the conductive particles 3. That is, the conductive particles 3 are in contact with both the first electrode 42 and the second electrode 52.
[0073] In the connection structure 10, as described above, the opposing first electrode 42 and second electrode 52 are electrically connected via the conductive particles 3. This sufficiently reduces the connection resistance between the first electrode 42 and the second electrode 52. This allows the current to flow smoothly between the first electrode 42 and the second electrode 52, and allows the first electronic member 4 and the second electronic member 5 to fully exhibit their functions.
[0074] <Method of Manufacturing Connection Structure> The above-mentioned connection structure can be produced by a method comprising the steps of: placing the above-mentioned adhesive composition between a first electronic component having a first electrode and a second electronic component having a second electrode; and thermocompression bonding the first electronic component and the second electronic component via the adhesive composition to electrically connect the first electrode and the second electrode to each other.
[0075] 5 is a schematic cross-sectional view showing one embodiment of a method for producing a connection structure. As shown in FIG. 5(a), first, an adhesive film 1 (a film-like adhesive composition) is placed on a main surface 41a of a first electronic member 4. When the adhesive film 1 is laminated on a substrate (not shown), the adhesive film 1 side of the substrate is faced to the first electronic member 4, and a laminate of the substrate and the adhesive film 1 is placed on the first electronic member 4. When the adhesive film 1 has a first adhesive layer 1A and a second adhesive layer 1B as shown in FIG. 3, it is preferable to place the first adhesive layer 1A side in contact with the main surface 41a of the first electronic member 4 from the viewpoint of increasing the number of conductive particles captured between the opposing electrodes.
[0076] After the adhesive film 1 is placed on the main surface 41a of the first electronic member 4, the laminate of the adhesive film 1 and the first electronic member 4 may be pressurized in the lamination direction to temporarily connect the adhesive film 1 to the first electronic member 4. At this time, heating may be performed together with the pressurization.
[0077] 5(b), the second electronic component 5 is further placed on the adhesive film 1 placed on the first electronic component 4 so that the second electrode 52 faces the first electronic component 4 (i.e., the first electrode 42 and the second electrode 52 are placed opposite each other, and the adhesive film 1 is placed between the first electronic component 4 and the second electronic component 5). If the adhesive film 1 is laminated on a substrate (not shown), the substrate is peeled off and then the second electronic component 5 is placed on the adhesive film 1.
[0078] Then, the first electronic member 4 and the second electronic member 5 are thermocompression bonded via the adhesive film 1. The thermocompression bonding is performed, for example, by applying heat and pressure in the direction of arrow A in FIG. 5(b). By applying heat and pressure in the direction of arrow A, the adhesive film 1 is cured, and the first electrode 42 and the second electrode 52 are electrically connected to each other. As a result, a connection structure 10 as shown in FIG. 4 is obtained.
[0079] The pressure during thermocompression bonding may be, for example, 5 MPa or more and 20 MPa or less. The heating during thermocompression bonding may be, for example, 100° C. or more and 170° C. or less, 150° C. or less, or 130° C. or less. The pressure application time and heating time during thermocompression bonding may be, for example, 10 seconds or more and 60 seconds or less.
[0080] In the connection structure 10 obtained as described above, it is possible to bring the conductive particles 3 into contact with both the opposing first electrode 42 and second electrode 52, and the connection resistance between the first electrode 42 and the second electrode 52 can be sufficiently reduced.
[0081] By applying pressure while heating the adhesive film 1, the adhesive component 2 hardens and becomes an insulating material 7 while the distance between the first electrode 42 and the second electrode 52 is kept sufficiently small, and the first electronic component 4 and the second electronic component 5 are firmly connected via the connection portion 6. EXAMPLES
[0082] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0083] <Preparation of conductive particles A1 to A8 and a1 to a4> Conductive particles A1 to A8 and a1 to a4 were prepared as follows. (Preparation of conductive particles A1) Tetramethylolmethane tetraacrylate, divinylbenzene, and styrene were used as monomers, which were polymerized by suspension polymerization using a polymerization initiator (benzoyl peroxide) to obtain cores (average particle size: 5.0 μm). The cores were subjected to electroless Ni plating to obtain conductive particles having protrusions and a conductive layer formed of Ni (Ni layer, thickness: 60 nm). A layer formed of Pd having protrusions (Pd layer, thickness: 10 nm) was formed on the Ni layer of the conductive particles by displacement plating to obtain conductive particles A1.
[0084] (Preparation of conductive particles A2) The cores (average particle size: 3 μm) were subjected to electroless Ni plating to obtain conductive particles A2 having protrusions and a conductive layer formed of Ni (Ni layer, thickness: 120 nm).
[0085] (Preparation of conductive particles A3) Cores (average particle size: 3.25 μm) were subjected to electroless Ni plating to obtain conductive particles A3 having protrusions and a conductive layer formed of Ni (Ni layer, thickness: 140 nm).
[0086] (Preparation of conductive particles A4) Conductive particles A4 having protrusions and a conductive layer formed of Ni-WB were produced by plating the surface of the core (average particle size: 3 μm) with Ni-WB.
[0087] (Preparation of conductive particles A5) The surface of the core (average particle size: 3 μm) was plated with Pd to obtain conductive particles A5 having protrusions and a conductive layer formed from Pd (Pd layer, thickness: 26 nm).
[0088] (Preparation of conductive particles A6) The cores (average particle size: 3 μm) were subjected to electroless Ni plating to obtain conductive particles A6 having protrusions and a conductive layer (Ni layer) formed from Ni.
[0089] (Preparation of conductive particles A7) The surface of the core (average particle size: 3 μm) was plated with Pd to obtain conductive particles A7 having protrusions and a conductive layer formed from Pd (Pd layer, thickness: 24.4 nm).
[0090] (Preparation of conductive particles A8) The cores (average particle size: 5 μm) were subjected to electroless Ni plating to obtain conductive particles A8 having protrusions and a conductive layer formed of Ni (Ni layer, thickness: 140 nm).
[0091] (Preparation of conductive particles a1) Cores (average particle size: 3 μm) were subjected to electroless Ni plating to obtain conductive particles a1 having protrusions and a conductive layer formed of Ni (Ni layer, thickness: 110 nm).
[0092] (Preparation of conductive particles a2) Conductive particles having protrusions and a conductive layer (Ni layer) made of Ni were obtained by electroless Ni plating of cores (average particle size: 3 μm). A layer made of Pd having protrusions (Pd layer) was formed on the Ni layer of the conductive particles by displacement plating to obtain conductive particles a2.
[0093] (Preparation of conductive particles a3) By applying Ni-P plating to the surface of the core (average particle size: 3 μm), conductive particles a3 were obtained that had protrusions, a conductive layer formed of Ni-P, and had the area ratio and average height of the protrusions as shown in Table 1.
[0094] (Preparation of conductive particles a4) Cores (average particle size: 3.8 μm) were subjected to electroless Ni plating to obtain conductive particles a4 having protrusions and a conductive layer formed of Ni (Ni layer, thickness: 120 nm).
[0095] <Analysis of conductive particles A1 to A8 and a1 to a4> (Protrusion area ratio) Conductive particles A1 to A8 and a1 to a4 were each collected on a carbon tape, and the collected conductive particles were imaged using a scanning electron microscope (SEM) to obtain SEM images including each conductive particle. The SEM images were analyzed using the method described in the section on the preferred embodiment of the invention to determine the area ratio of the protrusions of conductive particles A1 to A8 and a1 to a4. The results are shown in Table 1.
[0096] (Compression hardness at 20% compression) The compression hardness of the conductive particles at 20% compression was determined by the following method. A microcompression tester (Fisher Instruments, HM2000) was prepared, and conductive particles were scattered on a slide glass (Matsunami Glass Industrial Co., Ltd., S1214) on a stage set at 25°C. One particle was selected from the sample and compressed from the center at a speed of 0.33 mN / sec with an initial load of 0.1 mN using a prismatic diamond indenter with a square base of 50 μm on each side. The stress-strain curve was obtained. The load value when the particle diameter was deformed by 20% (at 20% compression) was read, and the compression hardness of the conductive particles at 20% compression was calculated using the following formula. The results are shown in Table 1. Compression hardness of conductive particles when compressed to 20% =(3 / √2)×F 20 ×S 20 -3 / 2 ×R -1 / 2 ×10 -3 R: Radius of conductive particle (μm), S 20 : Displacement at 20% compression (mm), F 20 : Load at 20% compression (N)
[0097] <Example 1> (Synthesis of polyurethane acrylate (UA1)) Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser having a calcium chloride drying tube, and a nitrogen gas inlet tube, 2500 parts by mass (2.50 mol) of poly(1,6-hexanediol carbonate) (trade name: Duranol T5652, manufactured by Asahi Kasei Chemicals Corporation, number average molecular weight 1000) and 666 parts by mass (3.00 mol) of isophorone diisocyanate (manufactured by Sigma-Aldrich Co.) were uniformly dropped over 3 hours. Next, after sufficient nitrogen gas was introduced into the reaction vessel, the inside of the reaction vessel was heated to 70 to 75°C to cause a reaction. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (Sigma-Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (Sigma-Aldrich) were added to the reaction vessel, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (Sigma-Aldrich) were added and reacted at 70°C for 6 hours under air atmosphere. This resulted in polyurethane acrylate (UA1). The weight-average molecular weight of polyurethane acrylate (UA1) was 15,000. The weight-average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150S manufactured by Resonac Technoservice Co., Ltd. Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94 x 106 Pa (30 kgf / cm2) Flow rate: 1.00mL / min
[0098] (Method for preparing polyester urethane resin) In a stainless steel autoclave equipped with a heater equipped with a stirrer, a thermometer, a condenser, a vacuum generator, and a nitrogen gas inlet tube, 48 parts by mass of isophthalic acid and 37 parts by mass of neopentyl glycol were put in, and 0.02 parts by mass of tetrabutoxy titanate as a catalyst was further put in. Then, the temperature was raised to 220°C under a nitrogen stream, and the mixture was stirred for 8 hours. Then, the pressure was reduced to atmospheric pressure (760 mmHg), and the mixture was cooled to room temperature. This caused a white precipitate to precipitate. Next, the white precipitate was taken out, washed with water, and then vacuum dried to obtain a polyester polyol. After the obtained polyester polyol was thoroughly dried, it was dissolved in MEK (methyl ethyl ketone) and put into a four-neck flask equipped with a stirrer, a dropping funnel, a reflux condenser, and a nitrogen gas inlet tube. In addition, dibutyltin dilaurate was put in as a catalyst in an amount of 0.05 parts by mass relative to 100 parts by mass of polyester polyol. Furthermore, 4,4'-diphenylmethane diisocyanate in an amount of 50 parts by mass relative to 100 parts by mass of the polyester polyol was dissolved in MEK and added using a dropping funnel, and the mixture was stirred at 80°C for 4 hours to obtain a polyester urethane resin.
[0099] (Preparation of First Adhesive Composition) As the polymerizable substance, 17 parts by mass of dimethylol tricyclodecane diacrylate (product name: DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.), 30 parts by mass of the polyurethane acrylate synthesized as described above, and 1.5 parts by mass of ethylene oxide-modified phosphate dimethacrylate (product name: PM-21, manufactured by Nippon Kayaku Co., Ltd.) were used, and as the curing agent, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane (product name: Perhexa 25O, manufactured by NOF Corporation) was used. A first adhesive composition was obtained by mixing 2.5 parts by mass of 3-glycidoxypropyltrimethoxysilane (product name: SH-6040, manufactured by Dow Corning Toray Co., Ltd.) as a silane coupling agent, 45 parts by mass of the polyester urethane resin prepared as described above as a thermoplastic resin, 2.8 parts by mass of 3-glycidoxypropyltrimethoxysilane (product name: SH-6040, manufactured by Dow Corning Toray Co., Ltd.) as a silane coupling agent, 2.5 parts by mass of Aerosil (product name: MR-202, manufactured by Nippon Aerosil Co., Ltd.) as a filler, and 26 parts by mass of the conductive particles produced by the above method. The content of the conductive particles, based on the total volume of the first adhesive composition, was 4% by volume. (Preparation of Second Adhesive Composition) As the polymerizable substance, 30 parts by mass of dimethylol tricyclodecane diacrylate (product name: DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.), 27.5 parts by mass of the polyurethane acrylate synthesized as described above, and 2.5 parts by mass of ethylene oxide modified phosphate dimethacrylate (product name: PM-21, manufactured by Nippon Kayaku Co., Ltd.) were used, and as the curing agent, 5.0 parts by mass of 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane (product name: Perhexa 25O, manufactured by NOF Corporation) and thermoplastic resin were used. A second adhesive composition was obtained by mixing 27.5 parts by mass of the polyester urethane resin prepared as described above as the resin, 15 parts by mass of a phenoxy resin (product name: Phenototo ZX-1356-2, manufactured by Nippon Steel Chemical & Material Co., Ltd.) as the resin, 5 parts by mass of 3-glycidoxypropyltrimethoxysilane (product name: SH-6040, manufactured by Dow Corning Toray Co., Ltd.) as the silane coupling agent, and 8 parts by mass of Aerosil (product name: R-202, manufactured by Nippon Aerosil Co., Ltd.) as the filler.
[0100] The first adhesive composition was applied to a substrate (PET film having a thickness of 50 μm) using an applicator to prepare a first adhesive layer. The second adhesive layer was prepared using the second adhesive composition in the same manner as the first adhesive layer. The first adhesive layer and the second adhesive layer were then bonded together using a laminator to prepare an adhesive film (thickness: 14 μm).
[0101] (Measurement of number density) Using an electron microscope, the size of the conductive particles in the adhesive film was measured. 2 The number of conductive particles per square was counted to determine the number density of the conductive particles in the adhesive film. The results are shown in Table 1.
[0102] (Preparation of electronic materials) The following electronic components were prepared: Glass materials A glass member was prepared that had a glass substrate and a Ti / Al / Ti wiring formed on the glass substrate. The thickness of the glass substrate was 0.7 mm, and the wiring in the glass member had a line width of 300 μm and an electrode height of 750 nm. Flexible Circuit Board (FPC) An FPC was prepared having a resin film substrate made of polyethylene terephthalate (PET) and wiring provided on the resin film substrate. The wiring of this FPC had electrodes consisting of a Cu layer with a pitch of 70 μm (space 35 μm, electrode width 35 μm, thickness 18 μm), a Ni layer with a thickness of 0.5 μm, and an Au layer with a thickness of 2.5 μm formed in that order on the Cu layer.
[0103] (Preparation of connection structure) The adhesive film of Comparative Example 1 was placed on a glass member, and an FPC was placed on the adhesive film to prepare a laminate of the glass member, the adhesive film, and the FPC. At this time, the main surface of the glass substrate (the surface on which the wiring was formed) and the main surface of the resin film base material (the surface on which the wiring was formed) were arranged so as to face each other. In addition, the first adhesive layer side of the adhesive film was arranged so as to contact the glass member. A silicone rubber cushioning material was placed on the surface of the FPC side of the prepared laminate, and the cushioning material was heated and pressed using a thermocompression bonding device (heating method: pulse heat type, manufactured by Ohashi Seisakusho Co., Ltd.) to prepare the connection structure of Comparative Example 1. The heating temperature was 120°C, the pressing pressure was 14 MPa, and the heating time and pressing time were 30 seconds. Here, the heating temperature means the set temperature of the thermocompression bonding device, and the pressing pressure means the pressure relative to the total connection area.
[0104] (Connection reliability under high temperature and humidity conditions) The obtained connection structure was subjected to a reliability test at 85°C and 85% RH. Specifically, first, the initial connection resistance between the electrodes of the glass member and the electrodes of the FPC in the connection structure was measured by a four-terminal method using a digital multimeter. Next, the connection structure was left in an environment of a temperature of 85°C and a humidity of 85% RH for 100 hours, and then the connection resistance (connection resistance after 100 hours) was measured by the same method as the initial connection resistance. In addition, the connection resistance increase rate was calculated by the following formula. The results are shown in Table 1. Connection resistance increase rate (%) = {(connection resistance after 100h - initial connection resistance) / initial connection resistance} x 100
[0105] <Examples 2 to 8 and Comparative Examples 1 to 4> Except for using the same amounts of conductive particles A2 to A8 and a1 to a4 prepared by the above method instead of conductive particles A1, adhesive films and connection structures were prepared in the same manner as in Example 1, and connection reliability was examined. The results are shown in Table 1.
[0106] [Table 1] [Explanation of symbols]
[0107] 1...adhesive film, 1A...first adhesive layer, 1B...second adhesive layer, 2, 2A, 2B...adhesive component, 3, 3A, 30A, 30B...conductive particles, 4...first electronic component, 5...second electronic component, 6...connection portion, 7...insulating material, 10...connection structure, 31...core, 32A, 32B...conductive layer, 32a...first conductive layer, 32b...second conductive layer, 33A, 33B...projection portion, 41...first substrate, 42...first electrode, 51...second substrate, 52...second electrode.
Claims
1. The conductive particles have a plurality of protrusions on the surface thereof. The compression hardness of the conductive particles when compressed by 20% is 350 kgf / mm 2 ~1500kgf / mm 2 and a ratio of an area of the plurality of protrusions to an area of the surface of the conductive particle is 30% or more; Adhesive composition.
2. a first electronic component having a first electrode; a second electronic component having a second electrode; a connection portion disposed between the first electronic member and the second electronic member, the connection portion electrically connecting the first electrode and the second electrode to each other; A connection structure, wherein the connection portion comprises a cured product of the adhesive composition according to claim 1.
3. The connection structure according to claim 2 , wherein at least one of the first electrode and the second electrode has a surface layer containing Au.
4. The connection structure according to claim 3 , wherein the surface layer has a thickness of 3 μm or less.
5. A step of disposing the adhesive composition according to claim 1 between a first electronic component having a first electrode and a second electronic component having a second electrode; and a step of thermocompression bonding the first electronic component and the second electronic component via the adhesive composition to electrically connect the first electrode and the second electrode to each other.
6. The method for manufacturing a connection structure according to claim 5 , wherein at least one of the first electrode and the second electrode has a surface layer containing Au.
7. The method for producing a connection structure according to claim 6 , wherein the surface layer has a thickness of 3 μm or less.
Citation Information
Patent Citations
Method for connecting semiconductor device
JP2000286299A
Adhesive composition and method for producing connected object
WO2018199329A1